PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. WEDU KABUPATEN MERAUKE - Nurwijayanti Nurwijayanti; Djabir Hamzah; Nurdjanah Hamid (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2019)
Human resources is one of the determinants of corporate success because the role of human resources as a valuable asset is to plan, implement and control various corporate operations. This study uses quantitative methods to examine the population or specific samples, random sampling in general and quantitative / statistical data analysis with the aim to test the hypothesis that has been established using the help of software SPSS 20.0. The result of this research found that partially leadership style and work environment have positive and significant influence to the satisfaction, leadership style and work environment have positive and significant effect to performance, job satisfaction have positive and significant effect to performance. while indirect influence shows the style of leadership and work environment have positive and significant influence to performance through satisfaction.